Impact of E-Banking Services with Customer Attitude & Satisfaction with Special Reference to Mumbai & Pune Region: Examining the Impact of E-Banking Services on Customer Attitude and Satisfaction in Mumbai and Pune Region (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today’s world is one with increasing online access to services. One part of this which is growing rapidly is online banking. Customer satisfaction is imperative for the incessant survival of any organization around the world. Purpose – This study aims to provide an analysis of the customer attitude and customer satisfaction toward three banking services technologies namely, automated teller machines (ATMs), mobile banking and internet (online) banking. The study started by conducting a correlation and Regression analysis, on the valid responses received from a convenience sample of bank customers. This research work intends to investigate the impact of E-banking variables on Customer Attitude and customer satisfaction in Mumbai Pune region. Data has been gathered through questionnaire from E-banking users as respondents, from different region in Mumbai Pune.